Development of a Spiritual Character-Based Curriculum to Improve Learning Quality in the Digital Era - Selvira Soaei Mahler; Aleandro Brances; Koimani Jeo; Attariq Khusairi; Mahosema Tui (International Journal of Education Management and Religion, 2024)
The development of a curriculum based on spiritual character is crucial in improving the quality of learning in the digital age. In the context of education increasingly influenced by technology, there is a challenge to ensure that students are not only academically intelligent but also possess strong moral and spiritual character. This study aims to examine the importance of integrating spiritual character values into the education curriculum and the wise use of technology to support holistic learning. The method used in this research is library research, which involves a literature study from various sources, including books, articles, and journals related to character education, spiritual character-based curriculum, and the use of technology in education. The spiritual character-based curriculum is designed to shape students who are not only competent in academics but also possess noble morals, empathy, and social responsibility. Through this approach, technology can be used as an effective tool to convey positive character values, such as through digital platforms, educational apps, and social media that are relevant to the lifestyle of today's students. The expected outcome of this curriculum development is to create a generation with a balance between intellectual intelligence and the strengthening of spiritual character, which in turn can help students face increasingly complex global challenges. As part of educational reform, the implementation of a spiritual character-based curriculum needs to be a priority in various educational institutions in Indonesia to ensure that education focuses not only on academic aspects but also on the formation of students' morals and character.